Asante Kete Drumming: A Musical Analysis of Meter, Feel, and Phrasing - Paulding, Benjamin. (2017)
Abstract: "Asante Kete Drumming: A Musical Analysis of Meter, Feel, and Phrasing" centers around three primary contributions: 1) synthesizing the published literature on Kete, 2) establishing frameworks for analysis through a close study of the dawuro timeline, and 3) analyzing Attah Poku's pedagogical version of one Kete piece - Kuakuanisuo. Additionally, it delivers an argument for representing the main body of Kete drumming in a ternary-quadruple meter equivalent to 12/8, felt in the half-time 2-feel. While the most substantial musical analysis of Kete to date - James Koetting's 1970 UCLA masters thesis - primarily serves to document alignment of instrumental parts, this thesis seeks to build from the Kete scholarship of Nketia, Koetting, Anku, Younge, and Ampene, and move towards an ethnographically informed musical analysis of Asante Kete drumming, focused on meter, feel, and phrasing.; Thesis (M.A.)--Tufts University, 2017.; Submitted to the Dept. of Music.; Advisor: David Locke.; Committee: Kwasi Ampene, and Stephan Pennington.; Keyword: Music.